Model Pemidanaan Integratif Dalam Rangka Mengembalikan Kerugian Negara Akibat Tindak Pidana Perikanan - Tuti Widyaningrum (Jurnal Hukum PRIORIS, 2017)
The maritime sector is a priority in developing the current government. The development of this maritime shaft is a consequence of the Indonesian state which is a largely marine territory. One of the maritime sectors is fisheries. Fisheries are a mainstay in increasing Indonesia's credibility in the eyes of the world. But the Indonesian fishery products cannot be enjoyed by the fisherman. in fact many of Indonesian’s fishery produce are stolen by foreign fishermen and many illegal vessels. As a result of illegal fishing, Indonesia has high potential losses. As a state that is a victim of illegal fishing is a state harmed. Other than the losses suffered by the state, threatened livelihoods means endangering a fisherman’s capability to meet his basic needs. Destructive fishing will also threaten the marine life. Law enforcement in the form of sinking of ships cannot restore the losses suffered by the state and its society. Similarly, the regulation to compensate illegal fishing is not clear enough, failing to deter its perpetrators. it’s important to find those integrative model of penalization to restore the State's Losses Caused of Fish Crime (Illegal Fishing)